Peer Teaching Method Integrated with Card Media: Its Implementation in Arabic Syntax Learning - Rizal, Muhammad; Al Farisi, Mohamad Zaka; Sopian, Asep (Institut Agama Islam Negeri Curup, 2023)
This research aimed to determine the effectiveness of peer teaching with card media in Arabic syntax learning. This goal was based on the problem of students' low abilities to understand Arabic syntax. These students’ low abilities were caused by the application of inappropriate learning methods and media while learning Arabic syntax. Moreover, this research also determined students' responses on the topic above. This research used a quasi-experimental design method with a non-equivalent control group design model. This research incorporated a sample of 58 students. Furthermore, the researchers collected the data using tests and questionnaires (with the Likert scale) and analyzed them with descriptive statistics and N-Gain test. The results showed that the average score of the N-Gain in the experimental group was 56.18; while the one in the control group was 17.87. The former was higher than the latter regarding students’ abilities in Arabic syntax. This indicated that peer teaching using card media was effective in Arabic syntax learning (especially in the moderate category). The questionnaire results also demonstrated that the average of students' responses to the application of the method above and media was 78.95%; hence it belonged to a positive category. This signifies that the method and media are of essential components in learning processes.